On the morphology and evolution of cicadomorphan tymbal organs. (March 2020) - Davranoglou, Leonidas-Romanos; Mortimer, Beth; Taylor, Graham K.; Malenovský, Igor
Abstract: Cicadas and many of their relatives (Hemiptera: Cicadomorpha) generate vibroacoustic signals using tymbal organs located on their first two abdominal segments. Although tymbals are well-studied in Cicadidae, their systematic distribution in other Cicadomorpha and their possible homologies to the vibroacoustic mechanisms of other Hemiptera have been debated for more than a century. In the present study, we re-examine the morphology of the musculoskeletal system of cicadomorphan vibroacoustic organs, and we document their systematic distribution in 78 species drawn from across the phylogeny of Cicadomorpha. We also compare their morphology to the recently-described snapping organ of planthoppers (Fulgoromorpha). Based on the structure and innervation of the metathoracic and abdominal musculoskeletal system, we find that several key elements of cicadomorphan vibroacoustic organs that have previously been assigned to the first abdominal segment in fact belong to the second. We find that tymbal organs are nearly ubiquitous in Cicadomorpha, and conclude based on their phylogenetic distribution, that they are likely to be synapomorphic. The unusual tymbal-like organs of the Deltocephalinae and Typhlocybinae, represent derived modifications. Finally, we propose a standardised terminology for sternal components of the cicadomorphan vibrational organs, which can be used in future taxonomic descriptions. Highlights: The segmental affinities of the tymbal musculoskeletal system are re-evaluated. Tymbals and tymbal-like organs are present across Cicadomorpha. The possession of tymbal-like organs is likely synapomorphic for Cicadomorpha. The homologies between tymbal organs and snapping organs require further study. We propose a new terminology for the cicadomorphan sternal sclerites and their apodemes.